Understanding The South China Sea: An Explorative Cultural Analysis - Evers, Hans (Penerbit Universiti Sains Malaysia (USM Press), 2014)
The South China Sea has attracted considerable attention among politicians, journalists and scholars since it has become a contested maritime space. Most works concentrate on conflicts and negotiations to resolve the ensuing issues. In this paper, a cultural theory will be applied to stress the importance of conceptions of space found in different cultures. The South China Sea is defined as "Mediterranean." By comparing it to other maritime spaces, like the Baltic and the Mediterranean Sea, lessons will be drawn from the "longue durée" of history, as analysed by French historian Fernand Braudel and from concepts of the cultural theory of Oswald Spengler. The paper will look at the South China Sea from two perspectives. The political perspective will discuss various events that have happened due to political tensions because of territorial demarcations, fishing rights and access to natural resources. Comparing three "Mediterranean seas," I shall argue that Mediterranean seas share certain properties that give rise to tensions and even armed conflict, but also solutions to its problems. The second perspective uses macro-sociology and cultural anthropology to classify and understand actions of the general population as well as political leaders when they ascertain property rights to Mediterranean seas.